Psychological Distress in Australian Clients Seeking Family and Relationship Counselling and Mediation Services. (2nd January 2014) - Petch, Jemima; Murray, Jennifer; Bickerdike, Andrew; Lewis, Pamela
<x xml:space="preserve">Abstract</x> There is little published data on the prevalence of psychological distress among individuals and couples seeking counselling and mediation services from non‐government organisations (NGOs). This national cross‐sectional study establishes the prevalence of psychological distress among clients seeking family and relationship counselling and mediation services from Relationships Australia. A national sample of 1, 365 clients attending services in April to May 2012 completed the 10‐item Kessler Psychological Distress Scale (K10) after their first counselling or mediation session. Individual counselling (M = 23.01, SD = 8.97, 95% CI [22.05–23.97]) and couple counselling (M = 21.63, SD = 8.10, [20.86–22.41]) clients reported a mean K10 score comparable to those reported by clinical studies of clients with anxiety or affective disorders. One quarter to one fifth of these clients reported very high psychological distress. Clients accessing mediation services had a mean score of 18.13 (SD = 7.76; [17.51–18.75]), and one tenth of clients reported very high distress. These elevated rates of very high psychological distress suggest that mental health issues may be a significant problem for a large proportion of clients accessing counselling and mediation NGO services provided under Family Support Programs (FSP) funding. Implications for screening for mental health and appropriate treatment planning are discussed.